A Bio-Inspired Algorithm for Virtual Machines Allocation in Public Clouds - Alhassan, Sarah; Abdulghani, Majed (Procedia computer science, 2019)
The rapid spread of cloud computing during the past few years has increased the need to improve cloud services. The infrastructure-as-a-service (IaaS) model is among the highly challenging cloud computing models that has been subject to many optimization proposals. In particular, the scheduling algorithms followed by IaaS resource management systems to allocate virtual machine requests to physical cloud severs play an important role in the performance of the entire cloud. This paper proposes a distributed scheduling algorithm for IaaS cloud computing services by imitating the locust behavior in nature. The simulation results show that the proposed Locust algorithm reduces the average turnaround time of requests without compromising the server utilization.